Novel therapeutic approaches for various cancer types using a modified sleeping beauty-based gene delivery system. - In-Sun Hong; Hwa-Yong Lee; Hyun-Pyo Kim (PLoS ONE, 2014)
Successful gene therapy largely depends on the selective introduction of therapeutic genes into the appropriate target cancer cells. One of the most effective and promising approaches for targeting tumor tissue during gene delivery is the use of viral vectors, which allow for high efficiency gene delivery. However, the use of viral vectors is not without risks and safety concerns, such as toxicities, a host immune response towards the viral antigens or potential viral recombination into the host's chromosome; these risks limit the clinical application of viral vectors. The Sleeping Beauty (SB) transposon-based system is an attractive, non-viral alternative to viral delivery systems. SB may be less immunogenic than the viral vector system due to its lack of viral sequences. The SB-based gene delivery system can stably integrate into the host cell genome to produce the therapeutic gene product over the lifetime of a cell. However, when compared to viral vectors, the non-viral SB-based gene delivery system still has limited therapeutic efficacy due to the lack of long-lasting gene expression potential and tumor cell specific gene transfer ability. These limitations could be overcome by modifying the SB system through the introduction of the hTERT promoter and the SV40 enhancer. In this study, a modified SB delivery system, under control of the hTERT promoter in conjunction with the SV40 enhancer, was able to successfully transfer the suicide gene (HSV-TK) into multiple types of cancer cells. The modified SB transfected cancer cells exhibited a significantly increased cancer cell specific death rate. These data suggest that our modified SB-based gene delivery system can be used as a safe and efficient tool for cancer cell specific therapeutic gene transfer and stable long-term expression.